The assistance and development of an online attendance system at Integrated Islamic School Ibnu Hajar, Balikpapan - Totok Sulistyo; Karmila Achmad; Mariatul Kiptiah; Fatmawati Fatmawati; Desak Made Ristia Kartika (Community Empowerment, 2022)
The industrial Revolution 4.0 is the integration of cyber technology, and automation, to enhance the effectiveness and efficiency. Therefore, accessibility to the information can be done at any-time and anywhere through the availability of internet networks. The Integrated Islamic School Ibnu Hajar is the institution that manages early childhood education school, elementary school and junior high school. It needs information systems in managing employee and student presence record. The systems development processes are consisted of pre-development, system analysis, system design, system development, system training and testing, and system implementation. The results are multimedia based on information system and the application of presence (http://sim.ibnuhajarbpn.sch.id). The employee presence system using android and web app which can be done by displaying QR and scanning QR in e-billboard or displaying QR on the laser scanner.